Pengaruh Kafein Terhadap Short Term Memory Pada Mahasiswi di Prodi Psikologi - Tursina Tursina; Aminah Aminah (Jurnal Psikologi Terapan, 2019)
The purpose of this study was to determine the effect of caffeine on short term memory in students of the Psychology study program, Faculty of Medicine, University of Malikussaleh. better than those who do not consume coffee. The study was conducted on 15 students of Malikussaleh University Psychology aged 18-22 years using one group pre-test and post test design experiments. The results of the paired sample t test stated that there was an effect of caffeine on the participants' short term memory (M = 6.0667 SD = 0.25820) and after being given coffee (M = 11.0667 SD = 2.40436), t (29) = 7,554. The conclusion of this study is that caffeine increases short term memory. Future researchers are expected to increase the number of participants and control the room situation.